Improving Job Performance in the State Sector by Public Service Motivation and Job–Person Fit toward Sustainable Development - Dinh Nguyen, Hoa; Thanh Thi Do, Phuong; Thuc Vo Huynh, Quyen (Organizations and Markets in Emerging Economies, 2024)
Job performance in the state sector is essential for the sustainable development of an economy. However, previous studies on the relationship among public service motivation (PSM), person–job fit (PJF), and job performance have yielded inconsistent results. Therefore, this study aims to explore the correlations between PSM, PJF, and job performance, with a particular focus on the state sector. After an extensive literature review, this study utilized quantitative methods to examine the correlation between PSM, PJF, and job performance. The data were analyzed employing Structural Equation Modeling (SEM), utilizing a sample of 263 participants who work at social insurance agencies, which are the state public organizations that serve employees for social insurance and health insurance. Preliminary results indicate that PSM positively influences both in-role job performance and extra-role job performance within the state sector. Moreover, the results also indicate the mediating role of PJF in the correlation between PSM, in-role job performance and extra-role job performance. The research contributions provide theoretical evidence that PSM is one of the key factors in increasing job performance in the state sector. In addition, the practical implications are discussed to assist managers in improving job performance for the country’s sustainable development.
Keywords: public service motivation; person-job fit; in-role job performance; extra-role job performance